Le problème des réserves et la réassurance - Perrier, Pascal (Assurances, 1987)
Reserves are one of the most important items in an insurer's or reinsurer's balance sheet as they reflect their current liabilities. Establishing a reserve presents major problems, particularly when the claims settlement period must be taken into account, as is the case for public liability insurance. It is here that factors, both monetary and legal, such as fault, scope of damage, liability and inflation came into play.